2015
DOI: 10.1039/c5dt00140d
|View full text |Cite
|
Sign up to set email alerts
|

PZT-like structural phase transitions in the BiFeO3–KNbO3 solid solution

Abstract: Despite the high prominence of the perovskites BiFeO(3) and KNbO(3) the solid solution between the two has received little attention. We report a detailed neutron and synchrotron X-ray powder diffraction, and Raman spectroscopy study which demonstrates an R3c→P4mm→Amm2 series of structural phase transitions similar to that exhibited by the PbZrO(3)-PbTiO(3) solid solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…It has been suggested that chemical heterogeneity in the form of core-shell structures can introduce internal stresses and lead to broad asymmetric peaks. 62,63 Similar observations were made previously by Lennox et al 64 on the basis of neutron diffraction studies on BiFeO 3 -KNbO 3 solid solutions. It was suggested that regions consisting of different A-site and B-site ion ratios, as a consequence of chemical inhomogeneity, can lead to peak broadening.…”
Section: Structural Characterizationsupporting
confidence: 81%
“…It has been suggested that chemical heterogeneity in the form of core-shell structures can introduce internal stresses and lead to broad asymmetric peaks. 62,63 Similar observations were made previously by Lennox et al 64 on the basis of neutron diffraction studies on BiFeO 3 -KNbO 3 solid solutions. It was suggested that regions consisting of different A-site and B-site ion ratios, as a consequence of chemical inhomogeneity, can lead to peak broadening.…”
Section: Structural Characterizationsupporting
confidence: 81%
“…Nevertheless, those peaks are clearly asymmetric, ruling out a simple cubic symmetry, as also corroborated by the Raman spectra in Fig. 2 [8]. Similarly, for KNLF x=0.16, a secondary tetragonal phase is also present, which appears to be in broad agreement with the work by Kakimoto and co-workers [9].…”
Section: Resultssupporting
confidence: 87%
“…In 2003, Kakimoto et al (2005) investigated the (1-x)KNbO 3 -xLaFeO 3 system and found the crystal symmetry to change from orthorhombic to tetragonal at x = 0.02 and to cubic at x = 0.20. In 2015, Lennox et al (2015) investigated the (1-x)KNbO 3 -xBiFeO 3 system and found a Orthorhombic (Amm2) → Tetragonal (P4mm) → Rhombohedral (R3c) series of structural phase transitions, as shown in Figure 7D, similar to that exhibited by the PbZrO 3 -PbTiO 3 solid solution. In this system, the orthorhombic symmetry is maintained at least up to 20% mol BiFeO 3 as inferred from neutron diffraction data (Lennox et al, 2015).…”
Section: Solid Solutions and Doping Studies In Knmentioning
confidence: 76%
“…In 2015, Lennox et al (2015) investigated the (1-x)KNbO 3 -xBiFeO 3 system and found a Orthorhombic (Amm2) → Tetragonal (P4mm) → Rhombohedral (R3c) series of structural phase transitions, as shown in Figure 7D, similar to that exhibited by the PbZrO 3 -PbTiO 3 solid solution. In this system, the orthorhombic symmetry is maintained at least up to 20% mol BiFeO 3 as inferred from neutron diffraction data (Lennox et al, 2015). KN crystals exhibit unusual large mechanical coupling factors, k t , which presents a maximum value of 0.69 at 40.51 • away from the polar axis.…”
Section: Solid Solutions and Doping Studies In Knmentioning
confidence: 76%